Differential Killing of Salmonella enterica Serovar Typhi by Antibodies Targeting Vi and Lipopolysaccharide O:9 Antigen. - Peter J Hart; Colette M O'Shaughnessy; Matthew K Siggins; Saeeda Bobat; Robert A Kingsley; David A Goulding; John A Crump; Hugh Reyburn; Francesca Micoli; Gordon Dougan; Adam F Cunningham; Calman A MacLennan (PLoS ONE)
Salmonella enterica serovar Typhi expresses a capsule of Vi polysaccharide, while most Salmonella serovars, including S. Enteritidis and S. Typhimurium, do not. Both S. Typhi and S. Enteritidis express the lipopolysaccharide O:9 antigen, yet there is little evidence of cross-protection from anti-O:9 antibodies. Vaccines based on Vi polysaccharide have efficacy against typhoid fever, indicating that antibodies against Vi confer protection. Here we investigate the role of Vi capsule and antibodies against Vi and O:9 in antibody-dependent complement- and phagocyte-mediated killing of Salmonella. Using isogenic Vi-expressing and non-Vi-expressing derivatives of S. Typhi and S. Typhimurium, we show that S. Typhi is inherently more sensitive to serum and blood than S. Typhimurium. Vi expression confers increased resistance to both complement- and phagocyte-mediated modalities of antibody-dependent killing in human blood. The Vi capsule is associated with reduced C3 and C5b-9 deposition, and decreased overall antibody binding to S. Typhi. However, purified human anti-Vi antibodies in the presence of complement are able to kill Vi-expressing Salmonella, while killing by anti-O:9 antibodies is inversely related to Vi expression. Human serum depleted of antibodies to antigens other than Vi retains the ability to kill Vi-expressing bacteria. Our findings support a protective role for Vi capsule in preventing complement and phagocyte killing of Salmonella that can be overcome by specific anti-Vi antibodies, but only to a limited extent by anti-O:9 antibodies.